Approaches to eradicate absolute poverty in Guangdong Province, the People’s Republic of China - Wu, Jinhua (East Asia working papers)
Guangdong is the largest province by gross domestic product in the People's Republic of China. It faces remaining challenge on how the gains from absolute poverty eradication and rural revitalization will address relative poverty. The paper proposes the direction for the next steps.